A new simple morphology‐based risk score is prognostic in stage I/II colon cancers. (11th May 2016) - Märkl, Bruno; Märkl, Maximilian; Schaller, Tina; Mayr, Patrick; Schenkirsch, Gerhard; Kriening, Bernadette; Anthuber, Matthias
Abstract: A portion of stage I/II colon cancers (10–20%) exhibit an adverse clinical course. The administration of adjuvant chemotherapy is recommended only in certain high‐risk situations. However, these risk factors recently failed to predict benefit from adjuvant therapy. We composed a new morphology‐based risk score that includes pT1/2 versus 3/4 stage, vascular or lymphovascular invasion, invasion type according to Jass, tumor budding and paucity (less than two) of lymph nodes larger than 5 mm. The occurrence of each of these factors accounts for one point in the score (Range 0–5). This score was evaluated in a retrospective study that included 301 cases. The overall survival differed significantly between the three groups with median survival times of 103, 90, and 48 months, respectively. Multivariable analysis revealed morphology‐based risk—high risk and low risk—as the sole independent factors for the prediction of death. Morphology‐based risk scoring was superior to microsatellite status and NCCN risk stratification. This method identifies a group of patients that comprises 18% of the stage II cases with an adverse clinical course. Further studies are necessary to confirm its prognostic value and the possible therapeutic consequences. Abstract : A morphology‐based risk (MBR) score facilitates a stratification of stage I/II colon cancers into three prognostically different groups. It identifies 18% cases of stage II cancers with adverse clinical course, and superior to microsatellite status and NCCN risk stratification.